REVITALISASI MADRASAH TSANAWIYAH BERBASIS PESANTREN SEBAGAI PENGUATAN RELIGIUSITAS SISWA DI MADRASAH TSANAWIYAH NEGERI 3 KOTA SURABAYA - Khusmila Ilmamuna; M. Fazlurrahman Hadi; M. Arfan Mu’ammar (Universitas Islam Madura, 2023)
Islamic boarding school-based Madrasah Tsanawiyah is the latest innovation in continuing to foster an Islamic generation that remains under the Ministry of Religion. Later, madrasas became another form of schools with religious Islamic, because they were in the same area as Madrasas and Islamic Boarding Schools. The teaching system at the madrasah tsanawiyah in this country has started to rework the form of the pesantren system in order to realize the success of the baton in Islamic da'wah and apply Islamic religious teachings according to the guidance of Islamic Education in the Qur'an and Sunnah to its students without leaving the pesantren culture inherent in Indonesia. Madrasas can now reach achievements that even outperformed other public schools. The research method used is qualitative with a type of approach by collaborating with literature studies. The research results help the scientific world to answer the curiosity of researchers regarding the findings of steps to revive the role of a Madrasah Tsanawiyah Negeri 3 Surabaya City Islamic Boarding School program. As well as supporting factors for religious activities that strengthen the spirit and mentality of the students in it, so that it becomes a very important topic context for its purpose of strengthening the religious dynamism of students at State Madrasah Tsanawiyah in Indonesia. The implication of this research is that education practitioners, especially PAI teachers, can easily carry out an institutional revitalization in an education.